2014
DOI: 10.1007/s00467-014-2755-1
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of calcium, magnesium, phosphate, citrate, oxalate, and uric acid by healthy schoolchildren using a 12-h collection protocol

Abstract: We report data from urine samples collected by using a simplified collection protocol. The observed differences between children with and without a family history of lithiasis could justify that in population studies aimed at setting reference values, the former are excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
2
7
1
3
Order By: Relevance
“…It was shown that the urinary excretion of solutes caused an increased risk of lithiasis in children with a family history of urolithiasis. Therefore, it is advised that children with a family history of urolithiasis should be excluded from population studies aimed at setting reference values, such as this study 18 ; (6) there were no data on 24-h urine oxalate excretions, thus this may limit the ability to make meaningful correlations with diet; (7) we could not collect urine samples from patients with primary HO to confirm thresholds where disorders of oxalate metabolism, such as primary HO, might be more likely, and to determine the appropriate cut offs. Despite all these limitations, we think that a good data set of a reference range for morning urine oxalate creatinine ratios was provided with this study.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the urinary excretion of solutes caused an increased risk of lithiasis in children with a family history of urolithiasis. Therefore, it is advised that children with a family history of urolithiasis should be excluded from population studies aimed at setting reference values, such as this study 18 ; (6) there were no data on 24-h urine oxalate excretions, thus this may limit the ability to make meaningful correlations with diet; (7) we could not collect urine samples from patients with primary HO to confirm thresholds where disorders of oxalate metabolism, such as primary HO, might be more likely, and to determine the appropriate cut offs. Despite all these limitations, we think that a good data set of a reference range for morning urine oxalate creatinine ratios was provided with this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is true that a simplified method would be very much appreciated, especially by the patients themselves (and the parents). However, my conclusion is that the presented procedures by Sáez-Torres et al [3] still have too many pitfalls to be recommendable. The authors neither compared both the afternoon spot urine samples and also the overnight collection with 24-h urinary excretions, nor did the timed urine collection always correlate to the spot urine sample.…”
mentioning
confidence: 89%
“…Obviously a lot of questions need to be answered which form the background of the paper by Sáez-Torres and colleagues in a recent issue of Pediatric Nephrology [3].…”
mentioning
confidence: 99%
“…Próba podniesienia fosfatemii u opisywanej pacjentki (duża doustna podaż fosforanów) wiązała się ze wzrostem nerkowej utraty do wartości 2252 mg/dobę, tj. 102 mg PO 4 /kg cc/dobę (dla przypomnienia wydalanie dobowe u dzieci zdrowych w wieku poniemowlęcym rzadko przekracza 40 mg/kg cc./dobę: niemowlęta starsze 37±11,7 mg/kg cc/db [22], dzieci 5-6 lat 13,8-36,8 mg/kg cc/ db, 6-7 lat 13,2-35,6 mg/kg cc/db, 9-10 lat 8,8-31,8 mg/kg cc/db, 11-12 lat 11,6-32 mg/kg cc/db [23], u dorosłych 0,4-1,3 g/24 godz. [24]).…”
Section: Dyskusjaunclassified